2021
DOI: 10.1148/radiol.2021203082
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy after Large-Vessel Ischemic Stroke: Utilization, Outcomes, and Readmissions across the United States

Abstract: E ach year approximately 795 000 people experience a new or recurrent stroke, the fifth leading cause of death and the most common source of permanent disability in the United States. Ischemic stroke is responsible for 87% of all strokes (1). The first endovascular clot retrieval device was approved by the U.S. Food and Drug Administration in 2004, and endovascular treatment of patients with stroke evolved substantially during the next decade (2). In 2015, investigators in five multicenter randomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Hospital size, teaching status, and city status were defined by the NRD. Reasons for readmissions were grouped as previously described 10…”
Section: Methodsmentioning
confidence: 99%
“…Hospital size, teaching status, and city status were defined by the NRD. Reasons for readmissions were grouped as previously described 10…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the database depends on the administrative data collection from discharge summaries and medical billing departments, which is prone to human error 14 . The ICD codes used in this study were obtained from previously validated studies, and the ICD-10 code used for COVID-19 diagnosis was established in April 2020 15–20 . In addition, the admissions captured in NIS are specific to inpatient settings, which may result in undercounting the true prevalence of COVID-19 among CeAD, especially those of milder cases.…”
Section: Discussionmentioning
confidence: 99%
“…14 The ICD codes used in this study were obtained from previously validated studies, and the ICD-10 code used for COVID-19 diagnosis was established in April 2020. [15][16][17][18][19][20] In addition, the admissions captured in NIS are specific to inpatient settings, which may result in undercounting the true prevalence of COVID-19 among CeAD, especially those of milder cases. Follow-up data in NIS are not available and, therefore, the recurrence of COVID or development of pseudoaneurysm could not identified.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Brinjikji et al indicated a significant reduction in the use of MT in uninsured patients compared with those with private insurance. 6 Golnari et al 15 investigated thrombectomy rates, outcomes, and readmission across the United States between 2016 and 2017 using the NIS and National Readmission Database (NRD) and compared the results with those of the HERMES collaboration meta-analysis. 16 Golnari et al also found a similar rate of nonroutine discharge to our cohort of NIS from 2013-2018 (78.2% versus 78.0% for all thrombectomies, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The HERMES collaboration helped shed light on the efficacy of thrombectomy for AIS, while the 3 recent clinical trials (DIRECT-MT, DEVT, and SKIP) contributed to the literature by investigating the efficacy of MT alone compared with MT1IV-tPA. 4,5,15,20 [21][22][23] These results may further increase the use of MT alone during the next several years. We hope that future studies will evaluate trends and disparities of use as more data from randomized controlled trials become available.…”
Section: Future Implicationsmentioning
confidence: 99%